Factor Analysis of a Scale of Temperament Styles among University Students (Journal Of Educational and Psychological Researches, 2025)
The current research aims to investigate the temperament styles among undergraduate students in terms of gender and specialization. A sample of 544 male and female students was chosen randomly from the University of Karbala for the academic year 2023-2024. To achieve the research objectives, the researcher adopted the scale of temperament styles by Buss-Plomin (1984) as a research tool to collect the needed data. With the help of the Statistical Package for the Social Sciences (SPSS), the research reached a number of conclusions, recommendations, and suggestions.